Emotional regulation and clinical symptomatology when experiencing the illness of a close person. (29th March 2019) - Reis, Nelson; Fernandes, Isabel; Almeida, Telma C.; Ramos, Catarina
Abstract : Introduction: In human life, emotions have a central role the adaptive functioning and in healthy psychological development [1 ]. The emotional regulation difficulty is deeply related to the development of several psychological disorders, increasing the vulnerability of those who experience negative situations [2 ]. The main objective of the current study was to analyze the association between emotional regulation and clinical symptomatology in individuals who witnessed the illness of a close person. Materials and methods: The sample is composed by 318 Portuguese adults. Concerning the experience of witnessing the illness of a close person 141 (44.3%) participants responded positively. The majority of the participants were female ( n = 266, 83.6%), with ages between 18 and 89 years old ( M = 29.69, SD = 13.229). The participants responded online to the consent term, the sociodemographic questionnaire, the Scale of the Difficulties of Emotional Regulation [2 ], the Brief Inventory of Symotoms [3 ], Posttraumatic Stress Disorder Ckecklist-5 [4 ]. The study was conducted in accordance with the ethical principles outlined in the Declaration of Helsinki. Results: The following groups were compared to find statistically significant differences (G1: participants who witnessed the illness of a close person, G2: participants who did not witness that event). There were not statistically significant differences betewen the groups in emotional regulation [ F (1, 316) = .061, p = .806] and in clinical symptomatology and Posttraumatic Stress Disorder (PTSD) symptons [ F (1, 316) = .054, p = .816]. Analysing the relation between emotional regulation, clinical symptomatology and PTSD symptoms, there were statistical significant correlations in all variables. Regarding the correlation between emotional regulation and PTSD symptoms, there were a significant and negative association ( r = .57 ; p < .001). Concerning the correlation between emotional regulation and all of the subscales in clinical symptomatology, there were significant and negative associations (e.g. r = .41 p < .001 in the somatization subscale). Finally, there were significant and positive associations bettwen PTSD symptoms and all of clinical symptomatology subscales (e.g. r = .62, p < .001 in the somatization subscale). Discussion and conclusions: We verified that individuals with more difficulties of emotional resolution had more clinical symptoms and symptoms of PTSD, which is corroborated by the literature [2].